(untitled) (Construction Economics and Building, 2012)
The emerging focus on "best value" in construction projects entails several crucial and complex decision-making tasks for appropriate selection of capable contractors and consultants. In many ways and thus could be correspondingly achieved at different levels. Although traditional "price based" selection approaches are still preferred on various grounds such as simplicity and/or public accountability, they may well result in some "false economy" or missed opportunities for producing a better value. Furthermore, the lower significance of price as compared to the higher risk transference in project delivery methods such as Design-Build and Build-Operate-Transfer type arrangements render the purely "price based" approaches even less useful. Therefore a structured value focused selection approach is considered as beneficial for meeting the client’s goals and projct-specific needs. This paper presents discussions on some useful approaches to best value conceptualizations in "Source selection" perspectives, e.g. starting with the "right" selection of competent constructors in Design-Bid-Build type projects. Furthermore, a conceptualized basic framework for best value selection is also presented.